Management‐dependent effects of pollinator functional diversity on apple pollination services: A response–effect trait approach. Issue 12 (18th September 2021) - Roquer‐Beni, Laura; Alins, Georgina; Arnan, Xavier; Boreux, Virginie; García, Daniel; Hambäck, Peter A.; Happe, Anne‐Kathrin; Klein, Alexandra‐Maria; Miñarro, Marcos; Mody, Karsten; Porcel, Mario; Rodrigo, Anselm; et al.
Abstract: Functional traits mediate the response of communities to disturbances (response traits) and their contribution to ecosystem functions (effect traits). To predict how anthropogenic disturbances influence ecosystem services requires a dual approach including both trait concepts. Here, we used a response–effect trait conceptual framework to understand how local and landscape features affect pollinator functional diversity and pollination services in apple orchards. We worked in 110 apple orchards across four European regions. Orchards differed in management practices. Low‐intensity (LI) orchards were certified organic or followed close‐to‐organic practices. High‐intensity (HI) orchards followed integrated pest management practices. Within each management type, orchards encompassed a range of local (flower diversity, agri‐environmental structures) and landscape features (orchard and pollinator‐friendly habitat cover). We measured pollinator visitation rates and calculated trait composition metrics based on 10 pollinator traits. We used initial fruit set as a measure of pollination service. Some pollinator traits (body size and hairiness) were negatively related to orchard cover and positively affected by pollinator‐friendly habitat cover. Bee functional diversity was lower in HI orchards and decreased with increased landscape orchard cover. Pollination service was not associated with any particular trait but increased with pollinator trait diversity in LI orchards. As a result, LI orchards with high pollinator trait diversity reached levels of pollination service similar to those of HI orchards. Synthesis and applications . Pollinator functional diversity enables pollinator communities to respond to agricultural intensification and to increase pollination function. Our results show that efforts to promote biodiversity provide greater returns in low‐intensity than in high‐intensity orchards. The fact that low‐intensity orchards with high pollinator functional diversity reach levels of pollination services similar to those of high‐intensity orchards provides a compelling argument for the conversion of high‐intensity into low‐intensity farms. Abstract : Pollinator functional diversity enables pollinator communities to respond to agricultural intensification and to increase pollination function. Our results show that efforts to promote biodiversity provide greater returns in low‐intensity than in high‐intensity orchards. The fact that low‐intensity orchards with high pollinator functional diversity reach levels of pollination services similar to those of high‐intensity orchards provides a compelling argument for the conversion of high‐intensity into low‐intensity farms.